Targeting cell adhesion molecules with nanoparticles using in vivo and flow-based in vitro models of atherosclerosis. Issue 8 (April 2017) - Khodabandehlou, Khosrow; Masehi-Lano, Jacqueline J; Poon, Christopher; Wang, Jonathan; Chung, Eun Ji
Atherosclerosis is a leading cause of death worldwide; in addition to lipid dysfunction, chronic arterial wall inflammation is a key component of atherosclerosis. Techniques that target cell adhesion molecules, which are overexpressed during inflammation, are effective methods to detect and treat atherosclerosis. Specifically, research groups have identified vascular cell adhesion molecule-1, intercellular adhesion molecule-1, platelet endothelial cell adhesion molecule, and selectins (E-selectin and P-selectin) as correlated to atherogenesis. In this review, we discuss recent strategies both in vivo and in vitro that target cell adhesion molecules. First, we discuss peptide-based and antibody (Ab)-based nanoparticles utilized in vivo for diagnostic, therapeutic, and theranostic applications. Second, we discuss flow-based in vitro models that serve to reduce the traditional disadvantages of in vivo studies such as variability, time to develop the disease, and ethical burden, but preserve physiological relevance. The knowledge gained from these targeting studies can be translated into clinical solutions for improved detection, prevention, and treatment of atherosclerosis. Impact statement: As atherosclerosis remains the leading cause of death, there is an urgent need to develop better tools for treatment of the disease. The ability to improve current treatments relies on enhancing the accuracy of in vitro and in vivo atherosclerotic models. While in vivo models provide all the relevant testing parameters, variability between animals and among models used is a barrier to reproducible results and comparability of NP efficacy. In vitro cultures isolate cells into microenvironments that fail to take into account flow separation and shear stress, which are characteristics of atherosclerotic lesions. Flow-based in vitro models provide more physiologically relevant platforms, bridging the gap between in vivo and 2D in vitro models. This is the first review that presents recent advances regarding endothelial cell-targeting using adhesion molecules in light of in vivo and flow-based in vitro models, providing insights for future development of optimal strategies against atherosclerosis.